0125 Dexmedetomidine Causes Age-Dependent Differences in the EEG Compared to NREM Sleep in B6 Mice. (12th April 2019) - Siegmann, Morgan J; Zachs, Dan; Kenny, Jonathan; Hozan, Moshen; Wilson, Matthew; Brown, Emery; Van Dort, Christa J
Abstract: Introduction: Dexmedetomidine (dex) is an alpha 2A adrenergic receptor agonist that is used clinically as a sedative. Dex is thought to induce sedation via disinhibition of the preoptic area which is similar to what occurs during non-rapid eye movement (NREM) sleep induction. Human, cat and rat electroencephalogram (EEG) studies have shown similarities between NREM sleep and dex induced sedation in delta power and spindle activity. We tested the hypothesis that dex induces changes in the EEG that are similar to natural NREM sleep in young adult and old B6 mice. Methods: Male B6 mice aged 4-5 months (young adult) and 10-18 months (old) were implanted for EEG/EMG recording from prefrontal cortex, parietal cortex and cerebellum. Seven days after the surgery mice received intraperitoneal saline (vehicle) or dex (50, 100, 200, 400 mug/kg) injections and electrophysiology was recorded for at least 4 hours. Wake, NREM, REM and sedation were visually scored. Spectral differences between dex sedation and NREM sleep were analyzed using Fourier based multitaper methods. Results: Dex induced dose dependent sedation and suppression of REM sleep in both young adult and old mice. Dex sedation produced from higher doses contained increased delta power for the first 90 minutes followed by attenuation of frequencies above 10 Hz compared to NREM sleep. Immediately following dex administration, high voltage spike waves were observed in the prefrontal cortex EEG for the first 10-15 minutes. High voltage spikes had a fundamental frequency of 3-3.5 Hz and were narrow with sharp peaks resembling epileptiform activity. Old mice had significantly more spikes than young adults. Conclusion: These data support the idea that dex induces a sedated state that is distinct from NREM sleep. The elderly or people prone to seizures may have increased spike activity when given dex. Support (If Any): none